Profiling of compounds in hydrosol extract of Aquilaria (agarwood) species using gas chromatography-mass spectrometry (GCMS) - Jaafar Ali, Natasha; Hashim, Yumi Zuhanis Has-Yun; Zainurin, Nur Aimi Aliah (2019)
For many years, most researches involving agarwood mainly focused on extracting the agarwood oil from the infiltrated resin, the most sought non-timber forest product from Aquilaria species which has high demand and prices. This led to other parts of this valuable plant species being considered as waste. Thisinclude the agarwood hydrosol (byproduct produced during the water distillation). Hydrosol has been reported to retain certain aromaticsof its primary essential oil. Therefore, the present study is conducted to identify the composition of the agarwood hydrosol extractsfromAquilaria species by using gas chromatography-mass spectrometry (GCMS). From the analysis, there were a total of 46, 48, 40, 53, 58 and 62 compounds detected in hydrosol extract samples of 1, 2, 3, 4, 5 and 6 respectively. Accordingly, the oxygenated and phenolic compounds were found to be present in all hydrosol extract samples. The detected phenolic compounds include Phenol, 2,5-bis (1,1-dimethylethyl)-,.Phenol, 2,4- bis (1,1-dimethylethyl)- and 9-Octadecenoic acid (Z)-, methyl ester. These compounds are believed to possess various potential biological activities including antioxidant activities. Sample 1 and 2 consistsesquiterpene compounds such as (-)- Aristolene, Naphthalene, decahydro-4a-methyl-1- methylene-7-(1-methylethylidene)-,(4aR- trans)-,Azulene,1,2,3,3a,4,5,6,7-octahydro-1,4-dimethyl-7- (1-methylethenyl)-,[1R- (1.alpha.,3a.beta.,4.alpha.,7.beta.)]- andalloaromadendrene where the later has the highest number of oxygenated and antioxidant compounds. To this end, it is noteworthy that findings from this study have unravel the potential medicinal benefits of agarwood hydrosol and thus realizing the waste to wealth paradigm.